Behavior of suicidal behavior in Cuba, 2011-2014. - Beatriz Corona Miranda; karen Alfonso Sagué; Liliam Cuellar Luna; Mariela Hernández Sánchez; Silvia Serra Larín (Universidad de Ciencias Médicas de La Habana, 2017)
Introduction:  Suicidal behavior includes suicidal attempt and consummated suicide.  804 000 deaths by suicide were registered in the world in 2012.  In Cuba, suicide is the ninth cause of death and the third one in the group of 10-19 years of age. Objective: To characterize suicidal behavior in Cuba from 2011 to 2014. Material and methods: The sampling universe was composed of all registries of mobidity by suicidal attempt and the registries of mortality by suicide, taken from the database of the Direction of Registry and Statistics of the Cuban Ministry of Public Health, from 2011 to 2014.  The variables were: sex, age for the attempt, skin color, occupation, and the method used for suicide. The accumulated morbidity and mortality rates were calculated by groups of ages per 100 000 inhabitants, the crude-, adequate-, -and sex-specific rates, the man-woman cause of mortality, and the attempt-suicide relationship.  The relative change (percentage) was calculated, as well as the percentages according to the variables. Results: 53 764 suicidal attempts were reported, for an accumulated rate of 126.2 per 100 000 inhabitants.  The female sex was 37 617 (70 %). The attempt-suicide relationship was 9.1. 5942 deaths by suicide were reported, for an accumulated rate of 14.8 per 100 000 inhabitants. The occupation that predominated was the retired one (29.8%), and the most used method was hanging (76.4%). Conclusions: The female sex is the most affected in the attempt, and the male sex is the most affected in the suicide. The attempt-suicide relationship decreases as age increases. Keywords: suicidal attempt, suicide, self-inflicted lesions, suicidal behavior.